Ultra-flexible high-k transparent integratable fully-carbon-based capacitor arrays for sharp-switching transistors. (September 2021) - Zhang, Yiming; Huang, Qiuyue; Huang, Weihong; Zhang, Min
Abstract: Investigating dielectric layer is one of the keys in realizing flexible transistors, which propose higher requirements and more challenges on electrical performance, mechanical flexibility, and integrability of the dielectric. The previously reported researches mainly focused on inorganic rigid dielectrics or organic intrinsically-flexible dielectrics could not meet the requirements effectively and efficiently. In this work, we propose a sandwich-like carbon nanotubes/graphene oxide/carbon nanotubes design, which is applicable to both passive and active devices. Adopting this design, we realize integratable fully-carbon-based ultra-flexible and transparent capacitor arrays (FC-UFT-CAs) for both metal-insulator-metal (MIM) and metal-insulator-semiconductor (MIS) types. The MIM FC-UFT-CA exhibits competitive dielectric performance with high permittivity of 8.5 and high capacitance density of 250 nF cm −2 . Significantly, the capacitance shows almost no degradation even after the bending radius is reduced to as small as 250 μm. And it keeps showing excellent electrical and mechanical properties after 10, 000 bending cycles under a radius of 1 mm. Based on the MIS FC-UFT-CA, fully-carbon-based transistors are realized, which show sharp-switching characteristic with an ultra-small subthreshold swing of 88 mV dec −1 . Overall, the proposed design and the fully-carbon-based devices provide a novel solution and show a great potential for further advancing flexible electronics. Graphical abstract: Image 1 Highlights: Flexible fully-carbon-based capacitor and transistor arrays have been achieved. Ultra-flexible high-k capacitors can endure bending radius as small as 250 μm. Sharp-switching transistors with subthreshold swing of 88 mV dec −1 .